Changing partners: transcription factors form different complexes on and off chromatin - Zongling Ji; Andrew D Sharrocks (Molecular Systems Biology)
Abstract The current knowledge on how protein–protein interactions regulate the function of transcription factors (TFs) has remained limited due to an incomplete knowledge of their interaction partners. In their recent work, Chen and colleagues (Li et al, 2015) analyse the interactome of 56 TFs and reveal distinct chromatin‐associated and soluble TF complexes.